Compaction and Plasticity Comparative Behaviour of Soft Clay Treated with Coarse and Fine Sizes of Ceramic Tiles - Al-Bared, M.A.M. (EDP Sciences, 2018)
Recycled blended ceramic tiles (RBT) is a waste material produced from ceramic tile factories and construction activities. RBT is found to be cost effective, sustainable, environmental-friendly and has the potential to be used as an additive in soft soil stabilization. Recent reports show that massive amounts of RBT are dumped into legal or illegal landfills every year consuming very large spaces and creating major environmental problems. On the other hand, dredged marine clay obtained from Nusajaya, Johor, Malaysia has weak physical and engineering characteristics to be considered as unsuitable soft soil that is usually excavated, dumped into landfills and replaced by stiff soil. Hence, this study investigates the suitability of possible uses of RBT to treat marine clay. Laboratory tests included Standard proctor tests and Atterberg limits tests. The plasticity of marine clay was evaluated by adding 10, 20, 30 and 40 of 0.3 mm RBT. In addition, the compaction behaviour of treated marine clay was compared by adding two different sizes (0.3 mm and 1.18 mm diameter) of RBT. For both coarse and fine sizes of RBT, 10, 20, 30 and 40 of the dry weight of the soft clay were added. The mixture of each combination was examined in order to evaluate the Maximum Dry Density (MDD) and the optimum moisture content (OMC) for the treated soft clay. MDD and OMC for soft untreated samples were 1.59 Mg/m3 and 22, respectively. Treated samples with 10, 20, 30 and 40 of 0.30 mm size RBT resulted in a significant reduction of OMC ranged from 19 to 15 while MDD resulted in increment ranged from 1.69 to 1.77 Mg/m3. In addition, samples treated with 10, 20, 30 and 40 of 1.18 mm size RBT resulted in major reduction of OMC ranged from 15 to 13.5 while MDD increased effectively from 1.75 to 1.82 Mg/m3. For all mix designs of soft clay-RBT, MDD was gradually increasing and OMC was sharply reducing with further increments of both sizes of RBT. Â© The Authors, published by EDP Sciences, 2018.